Pengenalan Budaya Thailand dan Madagaskar oleh Mahasiswa Program Bahasa Indonesia bagi Penutur Asing untuk Mahasiswa FMIPA Universitas Mulawarman: Introduction on Thai and Malagasy Cultures by Indonesian Language Program for Foreign Speakers Students for FMIPA Students, Mulawarman University - Subagyono, Raden Roro Dirgarini Julia Nurlianti; Zakaria, Masduki; Hasnee, Abdussalam; Laehtee, Chareef; Hama, Ailham; Aina, Ramanantsitoera Rojotiana Aron’ny (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
In the era of globalization and technological advancement, cultural and inter-country exchanges are becoming increasingly important, especially in education. Mulawarman University, through the Indonesian Language Program for Foreign Speakers (BIPA), took the initiative to introduce international culture to local students. One form of cultural introduction is through basic training on Thai and Malagasy cultures attended by FMIPA students. This activity aims to increase cross-cultural understanding, introduce cultural diversity, and build international collaboration in education. In the event held on April 22, 2025, BIPA students from Thailand and Madagascar provided basic training on their cultures through presentations and practices covering natural resources, culinary, and the language of their home countries. The event was also followed by an interactive discussion session between BIPA students and FMIPA students, which allowed for the exchange of information and learning experiences. Evaluation results showed that more than 80% of FMIPA students felt this activity increased their insight, curiosity, and appreciation of Thai and Madagascar cultures. This activity is expected to strengthen academic relationships between Indonesian and international students and enrich understanding of cultural diversity. This cross-cultural training serves as a reference for developing a collaborative intercultural learning model that benefits both BIPA learners and local students.